Syntaxin 11 is required for NK and CD8+ T‐cell cytotoxicity and neutrophil degranulation. Issue 1 (12th December 2012) - D'Orlando, Orietta; Zhao, Fang; Kasper, Brigitte; Orinska, Zane; Müller, Jürgen; Hermans‐Borgmeyer, Irm; Griffiths, Gillian M.; Zur Stadt, Udo; Bulfone‐Paus, Silvia
<x xml:space="preserve">Abstract</x> Syntaxin 11 (STX11) controls vesicular trafficking and is a key player in exocytosis. Since Stx11 mutations are causally associated with a familial hemophagocytic lymphohistio‐cytosis, we wanted to clarify whether STX11 is functionally important for key immune cell populations. This was studied in primary cells obtained from newly generated Stx11−/− mice. Our data revealed that STX11 is not only widely expressed in different immune cells, but also induced upon LPS or IFN‐γ treatment. However, Stx11 deficiency does not affect macrophage phagocytic function and cytokine secretion, mast cell activation, or antigen presentation by DCs. Instead, STX11 selectively controls lymphocyte cytotoxicity in NK and activated CD8+ T cells and degranulation in neutrophils. Stx11−/− NK cells and CTLs show impaired degranulation, despite a comparable activation, maturation and expression of the complex‐forming partners MUNC18–2 and VTI1B. In addition, Stx11−/− CTLs and NK cells produce abnormal levels of IFN‐γ. Since functional reconstitution rescues the defective phenotype of Stx11−/− CTLs, we suggest a direct, specific and key role of STX11 in controlling lymphocyte cytotoxicity, cytokine production and secretion. Finally, we show that these mice are a very useful tool for dissecting the role of STX11 in vesicular trafficking and secretion.